Model for determining the adequacy of drinking water intake in the Nambo coastal area of Indonesia - Tasnim Tasnim; La Ode Saafi; Kadek Ayu Karuniawati; Fitri Fitri; Nuzul Wahyuning Tias; Ririn Putri Handayani; Indriani Indriani; Eka Putri Saripati; Wa Ode Fitra Saripati (Healthcare in Low-resource Settings)
The availability of drinking water in the Nambo coastal area is still challenging, leading to inadequate water intake. This research investigates a model for evaluating the adequacy of drinking water consumption in the Nambo coastal area. The study employs a quantitative cross-sectional design involving 100 participants aged 15 years and older. Data analysis was conducted using the partial least squares structural equation modeling (PLS-SEM). The findings indicate that a person's belief has a positive and moderate effect on their water intake (p=0.000; R2=0.352; CI 97.5%: 0.179-1.531). This belief mediates the person's knowledge and attitudes about the importance of staying hydrated (p=0.046; R2=0.226; CI 97.5%: -0.005-0.440). Additionally, knowledge positively and moderately affects individual attitudes (p=0.000; R2=0.369; CI 97.5%: 0.226-0.635). Belief also has a positive and moderate influence on health maintenance (p=0.000; R2=0.428; CI 97.5%: 0.189-0.604). In conclusion, personal beliefs about the benefits of drinking water are critical to increasing water intake. Confidence in these beliefs stems from knowledge and positive attitudes toward the health benefits of water.